Didactical analysis of a particular situation in French nursery schools: the ritual morning act - Garcion-Vautor, Laurence (Swiss Journal of Educational Research, 2018)
This article has two objectives: – to show which type of situation the teachers in French nursery schools set up in order that the pupils learn in this school, – to show that these particular situations can be analyzed with the concepts resulting from mathematical didactics, in particular that of «milieu for study». By building a stable «milieu», the morning ritual in nursery schools allows the teachers and the pupils to co-build a «milieu for study». However, within this framework, the pupils learn neither how to read, nor to calculate. They learn how to use the tools of our society in which we live. This is done before studying these same tools at the elementary school level.